1966
DOI: 10.2134/agronj1966.00021962005800020031x
|View full text |Cite
|
Sign up to set email alerts
|

Longevity and Dormancy in Seeds of Several Cool‐Season Grasses and Legumes Buried in Soil1

Abstract: Nine kinds of crop seeds were buried in the field at 1‐, 2‐, 3‐, 5‐, and 7‐inch depths in Saran mesh bags to determine seed longevity and dormancy. Generally, persistence and viability were lowest at the 1‐inch depth and increased with depth, with differential longevity among species. Seeds of perennial ryegrass declined in viability most rapidly; orchardgrass and chewings fescue lost their viability after three winters; Highland bentgrass and Oregon annual ryegrass retained considerable viability; and red clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Miller and Nalewaja (1990) {sites and years} A vena fatua L. Moss (1985) {experiments, treatments, and years} Alopecurus myosuroides Huds. Rampton and Ching (1966) Thomas et al (1986) . Nature of the response function was judged based on visual inspection of the data, and only cases in which sufficient data were available to make a judgment were included.…”
Section: Curve Depth Referencementioning
confidence: 99%
See 1 more Smart Citation
“…Miller and Nalewaja (1990) {sites and years} A vena fatua L. Moss (1985) {experiments, treatments, and years} Alopecurus myosuroides Huds. Rampton and Ching (1966) Thomas et al (1986) . Nature of the response function was judged based on visual inspection of the data, and only cases in which sufficient data were available to make a judgment were included.…”
Section: Curve Depth Referencementioning
confidence: 99%
“…In most of the studies cited in Table 2, seeds were enclosed in mesh packets or tubes before burial (Banting 1966, Rampton and Ching 1966, 1970, Zomer et al 1984, Kannangara and Field 1985, Harradine 1986, Leguizam6n 1986, Thomas et al 1986, Donald and Zimdahll987, Miller and Nalewaja 1990. This procedure kept seeds together at the desired depth in the soil profile, but it had the unfortunate consequence that seeds that could have produced seedlings were killed.…”
Section: Curve Depth Referencementioning
confidence: 99%
“…Our findings were similar for both species; most seeds germinated in the first 3 months after sowing, and of those remaining, most were dead or nonviable. These findings are supported by Rampton and Ching (1966), who found that PR had very limited capacity for longevity and by Garrison and Stier (2010), who found that KB seed bags planted in a similar manner quickly declined or ceased to exist within a year.…”
Section: Perennial Ryegrassmentioning
confidence: 62%
“…Buried seeds which remain viable for extended periods of time would constitute the major obstacle to certified seed production in previously cultured pastures (Rampton & Ching, 1966;. 1960) considered in situ germination in soils to be the primary means of dissipation of seeds buried up to a depth of 200 mm.…”
Section: Introductionmentioning
confidence: 99%